Insights from the genome sequence of a salmonella enterica serovar typhi strain associated with a sporadic case of typhoid fever in Malaysia - Yap, K.P.; Teh, C.S.J.; Baddam, R.; Chai, L.C.; Kumar, N.; Avasthi, T.S.; Ahmed, N.; Thong, Kwai Lin (2012)
Salmonella enterica serovar Typhi is the causative agent of typhoid fever, which causes nearly 21.7 million illnesses and 217,000 deaths globally. Herein, we describe the whole-genome sequence of the Salmonella Typhi strain ST0208, isolated from a sporadic case of typhoid fever in Kuala Lumpur, Malaysia. The whole-genome sequence and comparative genomics allow an in-depth understanding of the genetic diversity, and its link to pathogenicity and evolutionary dynamics, of this highly clonal pathogen that is endemic to Malaysia.